Long-term treatment of persistent disseminated Nocardia cyriacigeorgica infection - Özgenç,Onur (2014)
In this paper a disseminated persistent Nocardia cyriacigeorgicainfection in an immunocompetent patient is described. The patient's long-term treatment, as well as its implications for managing similar cases in the future, is emphasized. Presenting with high fever, multiple nodules, and ulcerative cutaneous lesions of body sites, the patient was treated with various antimicrobials. Under combined therapy, empyema and arthritis, leading to disseminated nocardiosis, were seen. The overall treatment course was 28 months. It can be concluded that the choice of the antibiotics and optimal duration of treatment are uncertain; therefore the treatment of nocardiosis requires expertise.